2011
DOI: 10.1002/jsfa.4288
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic acid concentrations in organically and conventionally cultivated spring and winter wheat

Abstract: Organically produced spring and winter wheat had significantly higher concentrations of ferulic and p-coumaric acid as well as the total phenolic acid content than conventional wheat, though the differences in the levels of phenolics were not large. However, these differences are probably caused mainly by smaller size of organic wheat kernels (lower TKW).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
55
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 39 publications
14
55
3
Order By: Relevance
“…These differences in the compositions of the sourdough microbiota resulted from a combination of determinants, including environmental contaminations (e.g., depending on farming system), parameters for sourdough preparation (the same for all flours), and chemical composition of the flours (variable for some constituents). As previously observed (57,58), the farming system affected the phytase activity of the flours and, especially, the content of phenolic acids. The farming system appears to have affected the phytase activity of the flours and, especially, their phenolic acid content.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These differences in the compositions of the sourdough microbiota resulted from a combination of determinants, including environmental contaminations (e.g., depending on farming system), parameters for sourdough preparation (the same for all flours), and chemical composition of the flours (variable for some constituents). As previously observed (57,58), the farming system affected the phytase activity of the flours and, especially, the content of phenolic acids. The farming system appears to have affected the phytase activity of the flours and, especially, their phenolic acid content.…”
Section: Discussionsupporting
confidence: 74%
“…The farming system appears to have affected the phytase activity of the flours and, especially, their phenolic acid content. Relevant concentrations of bound ferulic and sinapic acids were present in the organic flours (57). The highest abundance of the L. plantarum group was found in the doughs and sourdoughs made with these flours.…”
Section: Discussionmentioning
confidence: 93%
“…Among particular acids significantly greater were concentrations of gallic, p-cumaric and ferulic acids. Similar results were reported by Zuchowski et al (2011) who found that concentrations of total and ferulic acids were greater in grain of spring wheat cultivated in ORG than in CON farms. Since phenolic acids are synthesized by plants in response to different types of stress (Robbins, 2003), their greater concentration may indicate that due to the lower mineral fertilization and lack of chemical protection under organic system, plants respond to the environmental stress in the enhanced manner.…”
Section: Resultssupporting
confidence: 90%
“…In a previous study, similar results were obtained from phenolic acid concentrations in spring and winter wheat. 9 The results showed that the content of ferulic acid was higher than the other phenolic acids in WBPE-N9-4, which may be associated with the antioxidative activity of WBPE-N9-4. Moreover, in the ROS assay, the antioxidant activity of WBPE-N9-4 was very close to that of the positive control-ferulic acid (Fig.…”
Section: Uplc/tdq Analysismentioning
confidence: 84%